Mapping the body through pain, loss and trauma: overcoming violence against women through art. - Ferreira de Castro, Carla (FronteiraZ. Revista do Programa de Estudos Pós-Graduados em Literatura e Crítica Literária, 2021)
The present text deals with the deployment of images of a mutilated body as means of expressing, celebrating, and overcoming pain, loss and trauma. Based on a true story, a violent crime against a 52-year-old woman shot at point-blank by a former boyfriend, her 20-year-old daughter, trying to initiate a form of healing process, depicted in a series of photographs and literary references the unfathomed manner her mother’s life was shattered, on a February night in 2020. The visual story will be analysed under the notions presented by Maurice Merleau-Ponty, Susan Sontag, and Rita Charon, among others, bearing in mind the concepts of illness, perception, the body as narrative, and the underlying urge to produce an enduring artistic testament to illustrate and crystallize that epistemological break marking life before and after the tragedy.